Incomplete Kawasaki disease with muscular weakness and bladder retention: a case report - Yating Sang; Lili Luo; Lina Qiao (BMC, 2024)
Abstract Background Kawasaki disease (KD) is an acute systemic immune vasculitis affecting multiple organs and systems in children, and is prevalent in children under 5 years of age. Muscular weakness is a rare manifestation of KD, and only 11 pediatric patients with KD combined with muscular weakness have been reported, of which evidence of myositis was found in 2/3 of the patients, and 1/3 could not be explained by myositis, the mechanism of which is still unclear. Cases of KD combined with bladder retention are even more rare, and there has been only 1 case report of KD combined with bladder retention in a child with no previous underlying disease. Case presentation We report a 22-month-old Asian child with incomplete Kawasaki disease (IKD) who initially presented with fever and progressive muscular weakness in the lower extremities, followed by the bladder and bowel retention abnormalities and rapid onset of heart failure, respiratory failure and shock. The child developed coronary artery ectasia (CAA) without the main clinical features of KD such as rash, conjunctival congestion, desquamation of the extremity endings, orofacial changes and enlarged lymph nodes in the neck. Creatine kinase and electromyography were normal. Temperature gradually normalized and muscle strength recovered slightly after intravenous immunoglobulin. The child could be helped to walk after 1 week of aspirin combined with steroid therapy. Conclusions We present the case of a 22-month-old child with IKD. The child began with progressive muscular weakness in the extremities, followed by the bladder and bowel retention abnormalities, and rapidly developed heart failure, respiratory failure, and shock. Despite early failure to detect the disease, the child recovered rapidly and had a favorable prognosis. KD comorbidities with muscular weakness as the main manifestation are uncommon. This is the first case report of IKD combined with both muscular weakness and bladder and bowel retention, which may provide clinicians with diagnostic and therapeutic ideas, as well as a basis for future exploration of the mechanisms of KD combined with muscular weakness or bladder and bowel retention abnormalities.